Quantitative measurement and flow visualization of water cavitation in a converging-diverging nozzle - Schmidt, Aaron James (Kansas State University, 2016)
Cavitation is the change of a liquid to a two-phase mixture of liquid and vapor, similar to boiling. However, boiling generates a vapor by increasing the liquid temperature while cavitation generates vapor through a decrease in pressure. Both processes are endothermic, removing heat from the surroundings. Both the phase change and heat absorption associated with cavitation provide many engineering applications, including contributing to a new type of refrigeration cycle under development. Cavitation can occur at or below the vapor pressure; conditions that delay cavitation and allow for a metastable liquid are not well understood. A converging-diverging nozzle was designed and fabricated to create a low pressure region at the nozzle throat. The converging section of the nozzle increased the water velocity and decreased the pressure, according to Bernoulli’s principle. A cavitation front was formed slightly past the nozzle throat. The cavitation location suggested that the water was metastable near the nozzle throat. Flow through the system was controlled by changing the nozzle inlet and outlet pressures. The flowrate of water was measured while the outlet pressure was lowered. The flowrate increased as the outlet pressure dropped until cavitation occurred. Once cavitation initiated, the flow became choked and remained constant and independent of the nozzle outlet pressure. High-speed imagery was used to visualize the flow throughout the nozzle and the formation and collapse of cavitation in the nozzle’s diverging section. High-speed video taken from 1,000 to 35,000 frames per second captured the formation of the cavitation front and revealed regions of recirculating flow near the nozzle wall in the diverging section. Particle Image Velocimetry (PIV) was used to measure the velocity vector field throughout the nozzle to characterize flow patterns within the nozzle. PIV showed that the velocity profile in the converging section and throat region were nearly uniform at each axial position in the nozzle. In the diverging section, PIV showed a transient, high-velocity central jet surrounded by large areas of recirculation and eddy formation. The single-phase experimental results, prior to cavitation onset, were supplemented by Computational Fluid Dynamics (CFD) simulations of the velocity distribution using Fluent software.
Keywords: Cavitation; Particle image velocimetry; High-speed video; Flow visualization; Computational fluid dynamics